Study of Thrombolytic r-TPA Alteplase in Ischaemic Stroke Patients at Dr. Soetomo General Academic Hospital Surabaya - Diah Utari Madiningrum; Achmad Firdaus Sani; Sumarno Sumarno; Muhammad Thariq Nadhafi (AKSONA, 2026)
Highlight: Alteplase effectiveness depends on efficient in-hospital stroke care. Code Stroke optimization is needed to improve thrombolysis timelines.   ABSTRACT Introduction: Acute ischemic stroke is a leading cause of disability and mortality worldwide. Intravenous thrombolysis with recombinant tissue plasminogen activator (r-TPA, alteplase) is an effective treatment when administered within 3–4.5 hours of stroke onset. However, its utilization remains limited due to delayed hospital arrival, limited early recognition of stroke, and variations in hospital preparedness. Objective: This study provides real data on the use of intravenous alteplase thrombolysis and evaluates implementation by assessing dosing regimen, treatment timelines, potential drug-related problems, and the implementation of the Code Stroke program at Dr. Soetomo General Academic Hospital. Methods: This descriptive observational study analyzed secondary data from the medical records of 17 patients with acute ischemic stroke treated with intravenous alteplase between January 1, 2023 and April 30, 2024. Data collected included demographic characteristics, comorbidities, history of recurrent stroke, and length of hospital stay. Clinical outcomes were evaluated using National Institutes of Health Stroke Scale (NIHSS) scores, therapy timing and dosage, door-to-needle time, and door-to-imaging time. Results: Intravenous alteplase was administered at doses of 0.6 mg/kg (12%), 0.7 mg/k (12%), and 0.9 mg/kg (76%). Although all patients were treated within the recommended 3–4.5-hour therapeutic window after stroke onset, only 23% achieved a door-to-needle time of ≤60 minutes. Adverse events were limited to gingival bleeding (6%) and hematuria (12%). Conclusion: Intravenous alteplase thrombolysis at Dr. Soetomo General Academic Hospital has generally followed established guidelines. However, further optimization of the Code Stroke program is required to improve treatment timeliness.